Pengaruh Biji Palem Sebagai Bahan Tambah Agregat Kasar pada Beton Terhadap Kuat Lentur - Bhakti, Setya Panca Indra; Ridwan, Ahmad (Universitas Batanghari Jambi, 2024)
In the development of the construction world in the modern era like today, many studies are trying to find alternative materials both as added ingredients and substitutes for concrete dough mixtures. One of the ingredients that can be used as added material is palm seeds that have dried, because palm seeds have not been widely used and used, and make the population become waste around the community because when the palm fruit is dry it will fall scattered around the palm tree. Therefore, palm seed research is held as an added material for coarse aggregate in concrete, with the hope of reducing palm seed organic waste and also efforts to minimize the use of natural rock materials.This study aims to determine the results of the bending strength of normal concrete blocks with a size of 60cm x 15cm x 15cm with added palm seeds of 1.5% 2.5% 3.5%. And the results of the study are in normal concrete bending strength worth 4.298 Mpa, in the variant of added material 1.5% worth 3.501 Mpa, in the variant 2.5% worth 3.172 and in the variant 3.5% has a value of bending strength 2.961 Mpa. So the result of bending strength can be seen that the higher the percentage of added material palm seeds, the lower the bending strength. And in the percentage of added ingredients of palm seeds 1.5%, 2.5%, and 3.5% there is no increase in strength, palm seeds cannot be used as a substitute for coarse aggregate.